2022
DOI: 10.1177/15269248221122894
|View full text |Cite
|
Sign up to set email alerts
|

Overall Infectious Complications Related to Belatacept Conversion in Comparison to Tacrolimus in Kidney Transplant Recipients

Abstract: Introduction: Belatacept has demonstrated effectiveness for preventing rejection in kidney transplant and has a favorable side effect profile. Studies assessing long-term infectious complications with belatacept compared to tacrolimus are limited. Project Aims: The purpose of this program evaluation was to determine the proportion of patients who developed an infection when converted to belatacept compared to those on tacrolimus. Design: In this retrospective evaluation, kidney transplant recipients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…30 In addition, our study reported reassuring safety outcomes with a similar proportion of death, major adverse cardiovascular outcomes consistent with the literature, 31 and no excess risk of infection conversely with previous observational studies. 20,22 Last, in our study, we observed for the first time an improvement in allograft survival up to 7 years post-conversion after belatacept conversion compared with matched patients treated with CNIs while the projected allograft survival was similar before conversion at the time of matching using the qualified iBox system. 23 This result was consistent whether in the subgroup of patients with DGF, with DSA at the time of conversion, or transplanted from an expanded criteria donor.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…30 In addition, our study reported reassuring safety outcomes with a similar proportion of death, major adverse cardiovascular outcomes consistent with the literature, 31 and no excess risk of infection conversely with previous observational studies. 20,22 Last, in our study, we observed for the first time an improvement in allograft survival up to 7 years post-conversion after belatacept conversion compared with matched patients treated with CNIs while the projected allograft survival was similar before conversion at the time of matching using the qualified iBox system. 23 This result was consistent whether in the subgroup of patients with DGF, with DSA at the time of conversion, or transplanted from an expanded criteria donor.…”
Section: Discussionsupporting
confidence: 49%
“…[16][17][18][19] Therefore, belatacept conversion seems to be promising, despite the higher incidence of acute rejection and opportunistic infections. [19][20][21][22] However, these studies were based on small numbers of patients and have not investigated the long-term graft outcomes post-conversion. This may explain why the CNI avoidance strategy is not implemented in the majority of transplant centers worldwide in the case of CNI intolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor, Belatacept, a maintenance immunosuppressive agent increasingly used among kidney transplant recipients (KTR), has been associated with an increased risk of infections. [1][2][3][4] However, clinical outcomes of SARS-CoV-2 infected KTR on belatacept are unknown. We analyzed KTR on belatacept who had SARS-CoV-2 infection between March 12, 2020 and October 31, 2022.…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Kidney Transpla...mentioning
confidence: 99%
“…Fionna Feller 1,2 Marwan M. Azar 3 Jennifer Marvin 4 Elizabeth Cohen 4 Sarthak Virmani 5 Maricar Malinis 3 1…”
Section: Data Availability Statementunclassified